General report of the committee of direction (Bombay, 1955)
The All-India Rural Credit Survey, 1951-2, was conducted under the direction of a Committee which was appointed in August, 1951, by Shri B. Rama Rau, Governor of the Reserve Bank of India. The Committee, which consisted of Shri A. D. Gorwala (Chairman), Prof. D. R. Gadgil, Shri B. Venka tappiah and Dr N. S. R. Sastry (Member-Secretary), prepared a series of Reports of which The General Report has now been for about a year before the public. Some of the more import ant of the many recommendations made in this Report have gained added significance by reason of their substantial accept ance, as basis of future policy in the sphere of rural credit, by the Governments, Central and State, by the Reserve Bank itself and by various all-India bodies representative of official and non-official co-operative opinion. There has been a demand for a shorter version of the Report, not so short how ever as to obscure the argument or be a bare summary of facts and recommendations. This abridged edition is intended to meet that demand. It has been prepared, not by the Com mittee or under its guidance, but as a departmental publication of the Reserve Bank. While every attempt has been made to ensure adherence to the sense, and wherever possible even the words, of the original, the text of the fuller Report of the Committee remains the authoritative one in the event of con flict of meaning between it and the abridged version. It should also be mentioned that, in the process of curtailment, some of the chapters of The General Report have been combined under new titles. The chapter and paragraph numbers of the present book are therefore not the same as those of the full Report.
Keywords: Credit